Phytotoxicity of Cadmium and Lead in Hydrilla verticillata (l.f.) Royle - Abha Agarwal1*, Alka Singh1, Chandra Shekhar Kumar2 and (Journal of Phytology, 2011)
Aquatic plants are well known in accumulating and in concentrating heavy metals. Hydrilla verticillata (lf.) Royle was subjected to different concentrations of Cd and Pb. Various physiological parameters i.e. fresh weight, total chlorophyll, carotenoid, NR activity, protein and bioaccumulation were studied. At lower metal concentrations, an increase in total chlorophyll, protein, and NR activity was noticed but at higher concentration these parameter were decreased. Treatment with 20.0 mg/l Pb and 2.5 mg/l & 5.0 mg/l Cd found to be more toxic. The accumulation of these metals (Pb and Cd) by H. verticillata, was more at lower concentration than higher concentration.